Interdependence of Science and Social Context Through Lens of Banjar Culture Activities (Batimung): Convergent Model - Almubarak, Almubarak; Sriyati, Siti; Liliawati, Winny (Journal of Mathematics Science and Computer Education, 2024)
The integration of culture into science education serves as a bridge of knowledge, ensuring that students develop a comprehensive understanding of the scientific and social context and possess literacy as potential educators. The research objectives are to determine the following: 1) the topics that students are most interested in discussing in the context of "diversity," 2) the perspective of students on cultural integration in science learning, and 3) the interdependence of the context of science and the Batimung culture that is characteristic of South Kalimantan. The research methodology relies on a mixed-method with convergent model. Students in the 2020-2023 class of chemistry education comprised the sample. The data collection techniques comprise interviews, questionnaires, and literature reviews. According to the results, the scientific and social contexts are interconnected. The quantitative technique employed is a questionnaire that encompasses diversity aspects comprising a variety of topics. The results indicate that 1) the most desired subject matter for discussion is "the impact of the environment on an individual," with a 59% response rate; 2) cultural integration in science education is a critical endeavour; and 3) the Batimung culture demonstrates that the context of science and social (culture) are not only related but also mutually influential. The conclusion is that the context of science and social, particularly cultural aspects can be the most recent presentation in the teaching and profound interpretation of science through a cultural lens.